POLICE BRUTALITY TERHADAP KAUM AFRIKA- AMERIKA: PENGGUNAAN KEKUATAN DAN AKUNTABILITAS KEPOLISIAN DI MINNESOTA TAHUN 2020 - Kinanti, Tasya Putri; Dewi, Putu Ratih Kumala; Nugraha, A.A Bagus Surya Widya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2024)
This study aims to describe the causes of high rate of brutality committed by police officers in the United States state of Minnesota against African Americans using exploratory qualitative method. Since George Floyd's murder was uploaded to the internet in 2020, cases of racial-based violence committed by police officers have been in the spotlight. Based on data provided, cases of racial violence committed by police officers tend to be high in Minnesota. Therefore, the researcher applies the conceptual framework of the institutional theory of racism, accountability and police power, to look at the practices or policies of the police institution that disadvantage certain layer based on their race or ethnicity. This research then looks at the licensing of excessive use of force practices in the police institution, the ineffectiveness of the department and the loss of accountability of officers, and racist government and lawmakers in Minnesota.